PEMBERDAYAAN GURU DALAM PENGEMBANGAN PRESTASI SISWA - Ahmad Bashri (Universitas Negeri Surabaya, 2020)
Implementation of the assessment is still an obstacle at the level of implementing in schools, one of themfor Progressive Bumi Shalawat high school teachers, especially in making plans for the development ofstudent achievement, both at national and international levels. The superiority of this high school isunder the auspices of Pesantren Bumi Shalawat so that the empowerment of managers or teachers indeveloping student achievement will complement the quality of students with academic-spiritual character.The problem to be solved is the difficulty of teachers in developing and implementing instruments fordeveloping student achievement. Targets or goals to be achieved are 1) increasing partner understandingof student achievement, 2) developing student achievement development guidelines 3) partner responseduring the process of partner empowerment activities. Broadly speaking the method in this activity isdivided into three phases. The first phase is the preparation phase. At this stage, the preparation ofmaterials, instruments and examples of assessment will be carried out when implementing activitiesthrough FGDs between partners and PKM Unesa's team. The second phase is the implementation ofactivities that will be carried out through the provision of information, modeling, and practice by participantsto compile instruments for assessing student achievement development and practice of using instrumentsthat have been prepared (through workshops on student achievement grids). In the third phase, aworkshop on the preparation of evaluation instruments and a follow-up to improve student performancewas held and continued with evaluation and feedback on the things needed in this implementation activity.Data obtained in this activity are instruments for developing student achievement, test results andquestionnaire responses of trainees analyzed descriptively quantitative and descriptive qualitative. Theresults achieved were: 1) Participants have been able to compile student achievement programs and guidestudent achievement development through focus group discussion (FGD) forums; 2) Participants havebeen able to compile an achievement grid based on achievement that is targeted for the next five yearsbased on achievements that have been previously achieved; and 3) The instrument for evaluating andfollowing up on improvements made to students' achievements has been prepared by the participants. Theposttest results obtained that partners have experienced increased understanding of student achievementwith high grades. The participants' responses during the mentoring category were good.